Explorations in curriculum history research - Burlbaw, Lynn M.; Field, Sherry L. (Research in curriculum and instruction., 2005)
The book series, entitled "Research in Curriculum and Instruction", will focuses on a) considerations of curriculum practices at school, district, state, and federal levels, b) relationship of curriculum practices to curriculum theories and societal issues, c) concerns derived from curriculum policy analyses and from analyses of various curriculum advocacies, and d) insights derived from investigations into curriculum history. Although the series emphasizes the American curriculum scene, aspects of curriculum practice and theory embedded in non-US countries are not be overlooked. Furthermore, this series does not restrict its concern to general curriculum matters, but it draws explicit attention to curriculum issues relating to the several curriculum subjects.